Repeat treatment of organotypic airway cultures with ethyl methanesulfonate causes accumulation of somatic cell mutations without expansion of bronchial-carcinoma-specific cancer driver mutations - Wang, Yiying; Le, Yuan; Harris, Kelly L.; Chen, Ying; Li, Xilin; Faske, Jennifer; Wynne, Rebecca A.; Mittelstaedt, Roberta A.; Cao, Xuefei; Miranda-Colon, Jaime; Elkins, Lana; Muskhelishvili, Levan; et al. (Mutation research. Genetic toxicology and environmental mutagenesis, 2024)
The human in vitro organotypic air-liquid-interface (ALI) airway tissue model is structurally and functionally similar to the human large airway epithelium and, as a result, is being used increasingly for studying the toxicity of inhaled substances. Our previous research demonstrated that DNA damage and mutagenesis can be detected in human airway tissue models under conditions used to assess general and respiratory toxicity endpoints. Expanding upon our previous proof-of-principle study, human airway epithelial tissue models were treated with 6.25–100 µg/mL ethyl methanesulfonate (EMS) for 28 days, followed by a 28-day recovery period. Mutagenesis was evaluated by Duplex Sequencing (DS), and clonal expansion of bronchial-cancer-specific cancer-driver mutations (CDMs) was investigated by CarcSeq to determine if both mutation-based endpoints can be assessed in the same system. Additionally, DNA damage and tissue-specific responses were analyzed during the treatment and following the recovery period. EMS exposure led to time-dependent increases in mutagenesis over the 28-day treatment period, without expansion of clones containing CDMs; the mutation frequencies remained elevated following the recovery. EMS also produced an increase in DNA damage measured by the CometChip and MultiFlow assays and the elevated levels of DNA damage were reduced (but not eliminated) following the recovery period. Cytotoxicity and most tissue-function changes induced by EMS treatment recovered to control levels, the exception being reduced proliferating cell frequency. Our results indicate that general, respiratory-tissue-specific and genotoxicity endpoints increased with repeat EMS dosing; expansion of CDM clones, however, was not detected using this repeat treatment protocol. This article reflects the views of its authors and does not necessarily reflect those of the U.S. Food and Drug Administration. Any mention of commercial products is for clarification only and is not intended as approval, endorsement, or recommendation. •Time-dependent increases in mutation frequency were observed following EMS exposure in human airway epithelial tissue models.•CDM expansion, however, did not occur during the current repeat treatment protocol.•General, respiratory, and genotoxicity endpoints peak immediately after repeat dosing with EMS.•Varying recovery kinetics were observed for changes in multiple endpoints.